DNA viruses in human cancer: An integrated overview on fundamental mechanisms of viral carcinogenesis - Oliveira, Deilson Elgui de [UNESP] (Elsevier B.V., 2007)
The first experimental data suggesting that neoplasm development in animals might be influenced by infectious agents were published in the early 1900s. However, conclusive evidence that DNA viruses play a role in the pathogenesis of some human cancers only emerged in the 1950s, when Epstein-Barr virus (EBV) was discovered within Burkitt lymphoma cells. Besides EBV, other DNA viruses consistently associated with human cancers are the hepatitis B virus (HBV), human papillomavirus (HPV), and Kaposi sarcoma herpesvirus (KSHV). Although each virus has unique features, it is becoming clearer that all these oncogenic agents target multiple cellular pathways to support malignant transformation and tumor development. (c) 2006 Elsevier B.V.. All rights reserved.
Keywords: viral carcinogenesis; DNA viruses; cancer; Epstein-Barr virus; Kaposi's sarcoma-associated virus; human papillomavirus; simian virus 40 virus; hepatitis B virus